(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The presence of “big data”, or this massive amount of increasing data, offers both an opportunity as well as a challenge to researchers. A lot of progress has been made in developing the capability to process, store, and analyze big data In addition to the big data computing capability (in terms of processing and storing big data in a distributed fashion on a cluster of computers), the rapid advances in using intelligent data analytics techniques—drawn from the emerging areas of artificial intelligence (AI) and machine learning (ML)—provide the ability to process massive amounts of diverse unstructured data that is now being generated daily to extract valuable actionable knowledge. This provides a great opportunity to researchers to use this data for developing useful knowledge and insights.